2017
DOI: 10.1097/prs.0000000000003842
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Dermal Matrix in Immediate Expander/Implant Breast Reconstruction: A Multicenter Assessment of Risks and Benefits

Abstract: INTRODUCTION Acellular dermal matrix (ADM) has gained widespread acceptance in immediate expander/implant reconstruction due to perceived benefits, including improved expansion dynamics and superior aesthetic results. Although previous investigators have evaluated its risks, few studies have assessed the impact of ADM on other outcomes, including patient-reported measures. METHODS The Mastectomy Reconstruction Outcomes Consortium (MROC) Study used a prospective cohort design to evaluate patients undergoing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 26 publications
(29 reference statements)
1
89
2
1
Order By: Relevance
“…A recent multicentre prospective North American cohort study18 (1297 women) found no difference in complications and patient reported outcomes between two stage IBBR with and without acellular dermal matrix. Complications were defined as adverse, surgery related, postoperative events requiring additional treatment at two years, including re-operation or readmission to hospital and reconstructive failure (removal of the implant).…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 95%
“…A recent multicentre prospective North American cohort study18 (1297 women) found no difference in complications and patient reported outcomes between two stage IBBR with and without acellular dermal matrix. Complications were defined as adverse, surgery related, postoperative events requiring additional treatment at two years, including re-operation or readmission to hospital and reconstructive failure (removal of the implant).…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 95%
“…Despite the widespread adoption of mesh-assisted techniques, there is a paucity of high-quality evidence to support their safety or effectiveness [5][6][7][8]. Multicentre prospective studies have failed to demonstrate any difference in outcomes between single-stage direct-to-implant and two-stage techniques [9,10] or between two-stage reconstructions with and without mesh [11]. However, a recent Dutch multicentre randomised controlled trial (RCT) demonstrated significantly increased numbers of complications when single-stage direct-to-implant procedures were compared with traditional two-stage techniques [12] despite equivalent quality-of-life outcomes [13].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…A prospective multicenter study of 1328 reconstructions found a major complication rate of 19.1%, 10.5% infection rate, and 7.4% implant loss . Another multicenter assessment including 655 patients found a major complication rate of 22.4%, 11.3% infection rate, and 9.2% implant loss . A meta‐analysis including 16 studies found a skin flap necrosis rate of 10.9%, with 6.9% seroma‐ and 5.7% infection rate .…”
Section: Patient Tumor and Treatment Characteristicsmentioning
confidence: 99%